REASONING OF LIBERAL ISLAM: A STUDY ON ISLAMIC PERSPECTIVES IN LIBERAL ISLAM NETWORK JAKARTA - Yusa' Farchan (Balai Penelitian dan Pengembangan Agama Semarang, 2016)
The renewal of Islamic thinking continuously develops from time to time in Indonesia. This research tries to answer two main problems, they are: how are the reasoning or ideology developed by Liberal Islam Network (LIN)?; and how are LIN’s main ideas and their metamorphoses? The research applies qualitative method with hermeneutic approach. The data is collected by library research or text documentation. The data is collected on August 18th to August 29th 2015. The research finds that the ideas of Liberal Islam Network show significant liberal signs. From the ontology of text, in reading religious text, LIN’s assumptions are “the critics over the truth”. LIN applies humanistic approach in reading the religious texts. This is confirmed by LIN’s defense toward human’s dignity. From the aspect of theoretically analytical tools in reading religious texts, LIN applies social sciences, which are socio-historical analyses. LIN uses symbol or semiotics analyses to read the religious text. The main notions of LIN are: First, Islam changes, it is not static; second, context is the first and history is the latter. Here, in reading a religious text, LIN wants to place context (socio-history) proportionally; third, LIN intends to hold God in our ground and history. The metamorphoses of LIN’s ideas are: firstly is to oppose theocracy; secondly is to endorse democracy; thirdly is to endorse gender equality; fourthly is to contextualize religious doctrines; and fifthly is to support pluralism and freedom of thinking.